The Dynamics of Al-Irsyad Al-Islamiyah Educational Institution (1914-2000) - Sudarningsih, Sudarningsih; Ansori, M Afif; Andari, An An; Pribadi, Joko; Rosmawati, Rosmawati (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This study aims to determine the background of the establishment of the Al-Irsyad Al-Islamiyyah Educational Institution and the education system at the Al-Irsyad Al-Islamiyyah Educational Institution. The type of research used in this study is library research. The point is to answer the problem formulation, the author collects data from books, journals, scientific papers, and so on. The study also used an induction and deduction approach where the collected data was drawn to generalizations to conclusions. The results of this research are the background for the establishment of the Al-Irsyad Al-Islamiyyah Educational Institute. The organization was founded in 1914 by Sheikh Ahmad Surkati Al-Anshori, a great cleric from Mecca who came from Sudan. Al-Irshad Al-Islamiyyah focuses on education, teaching, social, and da'wah at the national level. Al-Irshad Al-Islamiyyah is committed to purifying the teachings of Islam, expanding science, and developing a civilized and Islamic moral society. Al-Irshad Al-Islamiyyah aims to purify tawhid, worship and amaliyah Islam. Engaged in education and da'wah. To realize this goal, AI Irsyad has established hundreds of formal schools and non-formal educational institutions throughout Indonesia. And in its later development, Al-Irshad activities also penetrated the health sector, by establishing several hospitals. The largest are currently Al-Irsyad Hospital in Surabaya and RS. Siti Khadijah in Pekalongan.